The Sacred in the Mud: On Downward Transcendence in Religious and Spiritual Experience - Yue Wu (Religions)
Although there has been an increasing focus on religious and spiritual experience in literary studies within the context of post-critical and post-secular movements, much of the research is framed around the idea of “upward transcendence” in redemption narratives. This focus tends to overlook the negative aspects of life, such as absurdity, meaninglessness, and existential anxiety. Furthermore, it frequently resonates with capitalist ideals that champion a “seamless existence” while dismissing the unrefined essence of materiality. This article engages in two main tasks: First, it emphasizes the negative dimensions of religious and spiritual experience, drawing on Slavoj Žižek’s interpretation of theological and non-theological literature. Second, it expands the definition and scope of religious and spiritual experience, proposing an alternative paradigm based on absurdity and meaninglessness. This paradigm, “downward transcendence,” rejects the redemptive promise of “ascension” and redefines the sacred by engaging with the disruptive and unsettling fabric of existence, reconstructing the coordinates of the sacred within the fissures of reality. Through the case study of Sartre’s Nausea, the article explores how existential absurdity and meaninglessness can reconfigure the sacred, particularly through marginality and the transformative potential of negative experiences. It ultimately proposes downward transcendence as a radical reimagining of spiritual and existential freedom.